Pendidikan Islami bagi Penyandang Autisme - Dwi Sari Usop; Lilik Kholisotin (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2017)
Education is important for humans, including people with autism. However, there are still many autistic people who have difficulty learning. One of the difficulties experienced is learning about Islam. The purpose of this study: 1). The Importance of Islamic Education for People with Autism in Palangkaraya City, 2). Islamic Education Model for the Autism in the City of Palangkaraya. the type of research used is qualitative research using narrative strategy. The Data collection is done by interview and documentation. Subjects in the study, are 1). Teacher, 2). Parents, 3). The religious figure, 4). Ministry of Religious Affairs of Palangka Raya City. The data analysis techniques used was descriptive analytics. The results obtained in this study emphasize that autistic people are still obliged to study religion, especially Islam. This is evident from the participation of people with autism in Islamic studies in schools. While at home, parents still teach their children about religion. The learning of Islam given is very varied through the process of guidance, equalization of treatment with peers, imitation of peer behavior, and murotal therapy of the Qur'an.